A GENERIC COMPUTER VISION TOOL FOR RECOGNISING HUMAN ACTIVITIES - Jacobs, Jacobus; Nel, Stephan (The South African Journal of Industrial Engineering, 2023)
A prominent application area in the domain of computer vision is human activity recognition, which involves automatically detecting people’s actions from video footage. In this paper, a generic decision support tool capable of performing human activity recognition by employing computer vision is developed. The objective of the decision support tool is to facilitate the analysis of video footage by learning to identify human activities from video footage. The decision support tool facilitates the processing of raw data, the training of a computer vision model in respect of the processed data, and the deployment of the trained computer vision model in respect of unseen video footage. This paper details a computerised implementation of the decision support tool in respect of a benchmark data set and real-world data set involving the cash replenishment process of a South African bank.